Pengujian Black Box pada Perangkat Lunak Sistem Penilaian Mahasiswa Menggunakan Teknik Boundary Value Analysis - Debiyanti, Debiyanti; Sutrisna, Sutrisna; Budrio, Budrio; Kamal, Alvin Kurnia; Yulianti, Yulianti (Teknik Informatika Universitas Pamulang, 2020)
With this student assessment application, if there is an error in the program, there will be losses for students and universities. The loss that is in the natural student, if this application has an error (trouble) then the student assessment process will be delayed and difficult in the calculation of the value of students and students will be late in obtaining the value. The losses are in the natural universities where students want a quick assessment process but the university cannot calculate quickly and precisely. Method used in this application use black box method with boundary value analysis technique. The boundary value analysis technique measures application's assessment if there is an error when entering data that will be tested in the field to determine the value has been valid or no more errors will be stored in the database. The test is done on the Student assessment form by measuring the upper limit value and lower limit value through several predefined stages for each of the columns in the form. Test results can be input to improve the application. The results of this test can provide reference to the quality testing of the student assessment application by analyzing the functionality of the programs that have been made in accordance with the results expected